Глобалізаційні процеси та розвиток соціальної держави - Сковронський, Д. (Видавництво Львівської політехніки, 2016)
В умовах глобалізації посилюються суперечності у взаєминах соціальної держави і громадянського суспільства, що призводить до кризи соціальної держави. Криза відбувається на глобальному і національному рівнях. Однак, досягши балансу у взаємодії основних соціальних і політичних сил у суспільстві, ці суперечності можливо згладити. Цей баланс окреслює пріоритетні сфери і визначає заходи, які сприятимуть досягненню поставлених цілей. В условиях глобализации происходит усиление противоречий в отношениях социального государства и гражданского общества, что приводит к кризису социального государства. Кризис происходит на глобальном и национальном уровнях. Однако при достижении баланса во взаимодействии основных социальных и политических сил в обществе эти противоречия возможно сгладить. Этот баланс определяет приоритетные сферы и определяет меры, которые будут способствовать достижению поставленных целей. The concept of the welfare state have constitutions of France, Germany, Spain, Turkey, Macedonia, Slovenia, Croatia, Romania, Ukraine, Belarus, Russia, Armenia, Georgia, Kazakhstan, Tajikistan, Venezuela, Colombia, Paraguay, Ecuador, Gabon, Guinea, Congo, Niger, Rwanda, Senegal, Togo, Republic of Chad and others. In the context of globalization, the strengthening of social contradictions in relations between the state and civil society, leading to a crisis of the welfare state. The crisis is global and national levels. The globalization contributed to strengthening of the welfare state phenomenon over the last twenty years. However, these disputes may align by achieving balance in the interaction of the main social and political forces in society. This balance outlines priority areas and determines measures that will help to achieve the goals. In modern conditions the main challenges for the welfare state is its antinomic relationship with civil society and undermining its social base of globalization. Today Ukraine is going through difficult social and economic times in terms of hybrid war with Russia. There is a growing degree of social tension. Mass demonstrations, rallies, protests in many European countries become signs of recurrence and repeatability. In this context, the problem of establishing socially responsible democratic state becomes more and more controversial.
Глобализационные процессы и развитие социального государства
Globalization development and social state
Keywords: глобалізація; соціальна держава; демократичне суспільство; суспільна стабільність; соціальні конфлікти; глобализация; социальное государство; демократическое общество; общественная стабильность; социальные конфликты; globalization; the welfare state; democratic society; social stability; social conflicts